Can the intensity of game load affect the shooting performance in basketball? - Vencurik, T. (Journal of Human Sport & Exercise, 2016)
Victory in a basketball game depends on many factors. One of the main factors that determine game performance of the team is the successfulness of basketball shooting. The aim of this study is to determine the influence of the game load intensity on basketball shooting performance. Ten senior female basketball players (2nd division) participated in this study. Bleep test was used to set the maximal heart rate (HRmax) of each player. The intensity of game load was classified as follows: <75, 75-84, 85-95, >95 % of HRmax. During the two competitive games and the bleep test the HR was monitored by telemetric device. In the 1st zone no field goal attempt was recorded. In the 2nd zone the successfulness of shooting was 60%, in the 3rd zone 37.5% and in the 4th zone 45.2%. The relation between the successfulness of shooting and the individual zones was statistically insignificant (x2=2.786; df=2; p=0.24). Calculated Cramer`s contingency coefficient (V=0.149) shows weak strength of association. Based on the results we may conclude that the shooting performance in basketball game is not dependent on the intensity of game load. Besides the intensity of game load, the shooting performance can also be affected by many other factors. What is relevant for training process is that the 88.1% of all field goal attempts were made with HR over 85% of HRmax. This fact should be taken into consideration by coaches when planning shooting practice sessions.